2017
DOI: 10.1371/journal.pone.0170206
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of the Corrected Intraocular Pressure Obtained by the Corvis ST and Reichert 7CR Tonometers in Glaucoma Patients

Abstract: The purpose of the study was to investigate the accuracy of two corrected intraocular pressure (IOP) measurements by Corvis Scheimpflug Technology (CST)-IOPpachy and by corneal-compensated IOP (IOPcc) using the Reichert 7CR (7CR) tonometers. We also investigated the effects of corneal anatomical and structural parameters on the IOP measurements. The participants included 90 primary open-angle glaucoma patients. We assessed the IOP measurements, obtained by the CST, 7CR, and Goldmann applanation tonometer (GAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Ref. [ 7 ] reports that a reduced applanation (optical reflectance) signal width and/or amplitude perhaps indicate increased localized deformation, which would cause the optical detector to see a smaller reflectance area, similar to the corneal surface after LASIK [ 7 ]. ORA waveform of keratoconus patient showed a similar characteristic [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [ 7 ] reports that a reduced applanation (optical reflectance) signal width and/or amplitude perhaps indicate increased localized deformation, which would cause the optical detector to see a smaller reflectance area, similar to the corneal surface after LASIK [ 7 ]. ORA waveform of keratoconus patient showed a similar characteristic [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…ORA applies similar principle and reports two corneal biomechanical parameters termed Corneal Hysteresis (CH) and Corneal Resistance Factor (CRF) ( Figure 1 ). These two devices have their own advantages and limitations [ 7 ], and in this study, corneal biomechanical parameters in vivo are obtained based on ORA.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable results relative to GAT results for Goldmann-correlated intraocular pressure (IOPg) were obtained with the Reichert PT-100 (p=0.64) 7 and Reichert CR7 (p=0.52) even in patients with all pressure levels, although lower accuracy was achieved when considering the corneal-compensated IOP (IOPcc) modality in Reichert CR7 (p<0.01) ( Table 4 ). 18 …”
Section: Discussionmentioning
confidence: 99%
“…The Goldmann applanation tonometer (GAT) is presently the gold standard for clinical IOP measurements, and the traditional noncontact tonometer (NCT) is widely used in optometric practice as it is rapid and simple to operate with respect to measurement of IOP. Nevertheless, IOP readings increased as the CCT increased [2][3][4][5][6][7][8][9][10][11][12], axial length decreased [13,14], age increased [9,12], and the corneal curvature decreased [8,15] when the two tonometers are used.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we compared the IOPpachy-Corvis and the IOP obtained with GAT; it is named as IOP-GAT, and found that the two measurements were not interchangeable. This may be because IOPpachy-Corvis was not sufficiently unaffected by the ocular biomechanical parameters [11]. However, in 2016, Corvis ST developed a new parameter called biomechanically corrected IOP (bIOP-Corvis).…”
Section: Introductionmentioning
confidence: 99%